2010
DOI: 10.1021/jp908684c
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Chemistry in Inductively Coupled Plasmas for NO Removal from Mixed Gas Systems

Abstract: Inductively coupled rf plasmas were used to investigate the removal of NO from a variety of gas mixtures. Laser-induced fluorescence and optical emission spectroscopy were employed to measure the relative gas-phase density of NO as a function of the applied rf power, gas mixture, and catalytic substrate type. In general, the overall density of NO decreases as a function of applied rf power in both NO and N(2)/O(2) plasmas, but the addition of gases such as H(2)O vapor and CH(4), as well as the presence of Au-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In some cases, no specific formation and destruction of species were detected on the time scale of our system, further discussed below. Limitations of OES for reliable species density has been described in detail previously. ,, These include the observations that the actinometer and species of interest must undergo known electron impact excitation processes; be primarily excited from the ground state; optical emission branching ratios of lines of interest and other de-excitation pathways should be constant; and both species must have similar thresholds for the electron impact cross sections …”
Section: Methodsmentioning
confidence: 99%
“…In some cases, no specific formation and destruction of species were detected on the time scale of our system, further discussed below. Limitations of OES for reliable species density has been described in detail previously. ,, These include the observations that the actinometer and species of interest must undergo known electron impact excitation processes; be primarily excited from the ground state; optical emission branching ratios of lines of interest and other de-excitation pathways should be constant; and both species must have similar thresholds for the electron impact cross sections …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, T R trends observed in the present work appear to be somewhat different than other previously determined NO internal temperatures within our laboratory . Morgan et al performed LIF studies under a similar parameter space, reporting T R values of ∼350 K, regardless of pressure or power conditions for 100% NO plasmas.…”
Section: Resultsmentioning
confidence: 61%
“…Examining the excited state data, the 100 and 150 mTorr data are also similar, although the overall trend is a decrease in T V with increasing pressure. Our current work determining T V can again be compared to previous work by Morgan et al, wherein T V was reported for excited state NO species via OES analysis . Note that T R and T V values for the emission and absorbance of NO in 100% NO plasmas are summarized as a function of plasma parameters in the Supplemental Information, Tables S1 and S2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations